التنسيق الحضري المستدام لمسارات الشوارع في المدينة المعاصرة (حالة دراسية: التجربة البريطانية) - لفّاح, ماهر; قنصلية, جورج; حسين, جنان (Latakia University Journal -Engineering Sciences Series, 2016)
تعدت مفاهيم الاستدامة المستوى البيئي إلى المستوى العمراني التطبيقي، حيث تظهر محاولات جادة لإدراج مفهوم الاستدامة على كافة المستويات التخطيطية، التي لم تأخذ بعين الاعتبار المتطلبات الاجتماعية والاقتصادية والبيئية التي هي ركائز الاستدامة. يستعرض هذا البحث مفاهيم التنسيق الحضري في إطار الاستدامة، لما لها من أهمية في المدن المعاصرة، وأهم مبادئها التطبيقية، مع التركيز على مستوى مسارات الشوارع، كونها صلة التواصل والنقل بين التجمعات العمرانية والوظائف المختلفة، وكونها تسمح بتشكيل المشاهد الطبيعية الخاصة بهذه المسارات، حيث تتجاور فيها العناصر العمرانية مع العناصر الطبيعية. يتناول البحث بالتحليل التجربة البريطانية حول دور مسارات الشوارع في التنسيق الحضري المستدام للمدن والتجمعات العمرانية المختلفة في طبيعتها وتضاريسها، ويستخلص مجموعة من المؤشرات التي يمكن اعتمادها في التنسيق الحضري المستدام لمسارات الشوارع في المدن والتجمعات العمرانية السورية. The concept of sustainability has exceed the environmental level to the applied urban level where serious attempts to incorporate the concept of sustainability at all levels of urban planning, that didn’t take into consideration the social, economic, environmental requirements that are the basic elements of sustainability. In this research, we will insert the concept of designing sustainable urban landscaping because of its importance in Modern cities, and explaining the applied Categories especially on the “CORRIDORS” level because they connect & form the natural scene of the streets where the urban& natural elements are located next to each other. The research deals with the analysis of the British experience about the role of Corridors in Sustainable Urban Landscaping in urban areas & cities that are different in their nature & topography, and draws a set of indicators that can be adopted to coordinate Sustainable Urban Landscaping in cities & urban areas.